Analysis of Natural Aging Behavior of Asphalt Binder in Cold and Arid Region. (29th March 2022) - Song, Shanglin; Liang, Meichen; Hou, Fujin; Gao, Honggang; Bi, Yufeng; Zhang, Haixing; Guo, Meng
Abstract : With extremely bad climate and poor geographical environment in cold and arid region, the deterioration and failure of road materials are serious. In order to analyze the characteristics of natural aging behavior of asphalt binder in cold and arid region, the experiments were carried out based on the exposure field test base. The multiscale characterization of virgin asphalt under different natural aging conditions was carried out by means of macromechanical analysis and microchemical composition analysis. The results showed that the effects of natural aging and laboratory simulated aging on asphalt binder properties were similar. There was little effect on the performance of asphalt binder after natural aging one year. The effect of natural aging on asphalt binder in one year was similar to that of laboratory short-term aging. However, the strong UV radiation was a great challenge for asphalt pavement in Northwest China. Wind, dust, rain, and other factors have little effect on asphalt binder aging. Affected by the natural environment, macromolecular structures such as oxygen-containing polar functional groups will form in asphalt binder. The molecular weight of asphalt binder was increased, and the internal molecules of asphalt binder were subjected to large internal friction resistance in the process of movement. The macroscopic physical properties and road performance of asphalt binder become poor.